Komunitas Makro Alga di Perairan Pantai Desa Wakal, Kabupaten Maluku Tengah - Rosita Silaban (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2019)
Algae communities in life in the marine environment, among others, are used by various types of fish and other organisms as a place to live, forage, and spawn. Some types of macro algae also contain lime which plays a role in building coral reefs. As for humans, algae are used as food ingredients, both directly as vegetables and processed first as gelatin. The purpose of this study was to describe the composition of macro algae species found, to calculate density, population size, maximum biomass, and distribution patterns of macro algae communities in the coastal waters of Wakal Village. Taking algae macro samples is done by using the Linear Squares Transect method. Identification results of macro algae samples found 15 species classified into 3 divisions, 3 classes, 9 orders, 10 families, and 12 genera. The total density of macro algae species by individual is 2.86 ind / m2, with the highest density of species owned by Padina minor species and lowest Gelidiella acerosa, Galaxaura filamentosa, Halimeda opuntia, Ulva conglobata, Hypnea pannossa, Hypnea valentiae, and Acanthophora specifera. The total density of macro algae species based on biomass is 68.48 gr / m2 where Padina minor has the highest biomass density value and the lowest is Acanthophora specifera. The total population of macro algae based on individuals is 7.71 ind / ha, with Padina minor having the highest value of the highest and lowest population Gelidiella acerosa, Galaxaura filamentosa, Halimeda opuntia, Ulva conglobata, Hypnea pannossa, Hypnea valentiae, and Acanthophora specifera. The total macro population of algae based on biomass is 184.90 gr / ha with the highest biomass owned by species Padina minor and the lowest is Acanthophora specifera. The total maximum macro biomass of algae is 1008.18 gr / ha with the highest maximum biomass owned by species Padina minor and the lowest maximum biomass is owned by the species Acanthophora specifera. The pattern of macro spread of algae in Wakal Village is in groups (Ip = 0.5).